'Tinkers' Synge and the cultural history of the Irish traveller - Burke, Mary (Mary M.) (Oxford : Oxford University Press, 2009)
Irish playwright J.M. Synge created influential but misunderstood representations of travellers or 'tinkers'. This work traces the history of the 'tinker' back to medieval Irish historiography and English Renaissance literature and forward to contemporary US screen depictions.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Synge, J. M. -- 1871-1909 -- Criticism and interpretation; Irish Travellers (Nomadic people) in literature